2019
DOI: 10.1042/ebc20190014
|View full text |Cite
|
Sign up to set email alerts
|

Membrane dynamics in cell migration

Abstract: Migration of cells is required in multiple tissue-level processes, such as in inflammation or cancer metastasis. Endocytosis is an extremely regulated cellular process by which cells uptake extracellular molecules or internalise cell surface receptors. While the role of endocytosis of focal adhesions (FA) and plasma membrane (PM) turnover at the leading edge of migratory cells is wide known, the contribution of endocytic proteins per se in migration has been frequently disregarded. In this review, we describe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 89 publications
0
5
0
Order By: Relevance
“…Due to its ability to bind to and interact with such a diverse array of signalling molecules, it is unsurprising that Cav1 has been implicated as a major regulator of cell migration. [108][109][110][111] Immunostaining experiments show polarized Cav1 localization may be necessary for migration of endothelial cells, [112][113][114][115][116] where it binds to actin crosslinking protein filamin, suggesting that Cav1 may be modulating the cytoskeleton. In line with these findings, Cav1 has been shown to affect cytoskeletal remodelling and focal adhesion assembly by differentially affecting activity Rho family of GTPases, namely RhoA, Rac1 and Cdc42 through interaction with various guanine nucleotide exchange factors (GEFs) and GTPase activating proteins (GAPs).…”
Section: Cell Migrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to its ability to bind to and interact with such a diverse array of signalling molecules, it is unsurprising that Cav1 has been implicated as a major regulator of cell migration. [108][109][110][111] Immunostaining experiments show polarized Cav1 localization may be necessary for migration of endothelial cells, [112][113][114][115][116] where it binds to actin crosslinking protein filamin, suggesting that Cav1 may be modulating the cytoskeleton. In line with these findings, Cav1 has been shown to affect cytoskeletal remodelling and focal adhesion assembly by differentially affecting activity Rho family of GTPases, namely RhoA, Rac1 and Cdc42 through interaction with various guanine nucleotide exchange factors (GEFs) and GTPase activating proteins (GAPs).…”
Section: Cell Migrationmentioning
confidence: 99%
“…Due to its ability to bind to and interact with such a diverse array of signalling molecules, it is unsurprising that Cav1 has been implicated as a major regulator of cell migration . Immunostaining experiments show polarized Cav1 localization may be necessary for migration of endothelial cells, where it binds to actin cross‐linking protein filamin, suggesting that Cav1 may be modulating the cytoskeleton.…”
Section: Role Of Cav1 In Cellular Processes Crucial For Normal Skin Fmentioning
confidence: 99%
“…Although the plasma membrane separates the interior of the cell from the extracellular environment, there is a massive material transfer between both sides [59]. These materials typically are transported by vesicles which assemble large organelles within the cell cytoplasm called endosome.…”
Section: Resultsmentioning
confidence: 99%
“…The difference (≈ 18%–20% at E10.5) was also associated with differences in VAMP3 expression (increased in CH-derived CR cells with respect to PSB-derived ones). VAMP3 is involved in endocytosis, a crucial process that modulates membrane dynamics at the leading edge of migrating neurons and axons ( Kamiguchi and Yoshihara, 2001 ; Kawauchi, 2015 ) as occurs in other cell types ( Llanses Martinez and Rainero, 2019 ). In addition, the authors showed that CH-derived CR cells migrate towards the dorsal pallium while PSB-derived CR cells migrate laterally in the rostro-caudal axis ( Barber et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%